Day 2 Tue, August 28, 2018 2018
DOI: 10.2118/191080-ms
|View full text |Cite
|
Sign up to set email alerts
|

Development of Modified Rhizophora spp. Tannin Biopolymer Additive in Drilling Fluid System for High Temperature Well Applications

Abstract: The main objective of the current work is to investigate the performance of Rhizophora spp. tannin-lignosulfonate (RTLS) as a deflocculant in water-based drilling fluid (WBDF). Rhizophora spp. tannin (RT) was extracted from the barks, waste of conventional charcoal production. RTLS was synthesized and characterized by using Fourie transform infrared spectrometer (FT-IR) over a wide range of wavelength from 400 to 4000 cm−1 to determine the main functional group, and using thermogravimetric analysis (TGA) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…(Arunprabu and Ramanathan 2016). Extraction with hot water is more economical compared to extraction with methanol, as confirmed in several recent investigations (Ghazali et al 2018a;Vigneswaran et al 2018;Basyuni et al 2018). Thus, hot water was selected for the extractions of the RMTE deflocculant because it is safer, less harmful and cost effective.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…(Arunprabu and Ramanathan 2016). Extraction with hot water is more economical compared to extraction with methanol, as confirmed in several recent investigations (Ghazali et al 2018a;Vigneswaran et al 2018;Basyuni et al 2018). Thus, hot water was selected for the extractions of the RMTE deflocculant because it is safer, less harmful and cost effective.…”
Section: Resultsmentioning
confidence: 90%
“…Tables 3 and 4 show the per cent yields of CTE and HTE extracted with hot water, respectively. Previous researches revealed that tannin extracts from polymers are within the range of 60-80% for CTE and less than 40% for HTE (Ghazali et al 2018a;Arunprabu and Ramanathan 2016).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations